(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2020)
Education in the 21st century requires learning skills such as critical thinking, creativity, collaboration, and communication, which are essential in achieving quality education. The learning skills teach learners about the psychological procedures required to adjust to the constantly evolving concept of learning in today’s generation. One of the most significant skills children learn in primary school is reading. It is where learners gather information essential in everyday living and all areas. Reading is the foundation of learning and a gateway to success. Learners’ attitudes and interest in reading are important factors in motivating learners to have passion and love for reading. This study determined the reading status of Grade 5 learners as a basis for developing a reading workbook. This study utilized descriptive research with 260 learners as the respondents of the study who answered the reading attitude and interest survey. The reading profile of the respondents was determined using the Phil-IRI post-test result. The data were analyzed and presented employing both descriptive and inferential statistics. Results revealed that the learners’ reading profile was instructional and their reading attitude was very positive. In terms of reading interest, the majority of the learners were interested in fiction reading materials, motivated to read because of personal needs, fond of reading printed materials, and their reading scale showed that they were interested in reading. Furthermore, there was a substantial difference in reading comprehension, word recognition, reading platform, and reading interest scale between lowland and upland learners. Lastly, the reading attitude and reading interest of the learners were significant predictors of their reading profile. These findings suggest that the reading attitude and interest affect the reading profile of the learners. The more the learners show a positive attitude and a high interest in reading, the more fluent readers they become. Thus, a reading workbook was designed as a supplementary tool to enhance the reading profile of the learners and build independent reading skills.